Ultrasound-assessed diaphragm dysfunction predicts clinical outcomes in hemodialysis patients - Jing Zheng; Qing Yin; Shi-yuan Wang; Ying-Yan Wang; Jing-jie Xiao; Tao-tao Tang; Wei-jie Ni; Li-qun Ren; Hong Liu; Xiao-liang Zhang; Bi-Cheng Liu; Bin Wang (Scientific Reports, 2022)
Abstract Skeletal muscle atrophy is prevalent and remarkably increases the risk of cardiovascular (CV) events and mortality in hemodialysis (HD) patients. However, whether diaphragm dysfunction predicts clinical outcomes in HD patients is unknown. This was a prospective cohort study of 103 HD patients. After assessment of diaphragm function by ultrasonography and collection of other baseline data, a 36-month follow-up was then initiated. Participants were divided into diaphragm dysfunction (DD+) group and normal diaphragm function (DD−) group, according to cutoff value of thickening ratio (i.e. the change ratio of diaphragm thickness) at force respiration. The primary endpoint was the first nonfatal CV event or all-cause mortality. A secondary endpoint was less serious CV events (LSCEs, a composite of heart failure readmission, cardiac arrhythmia or myocardial ischemia needed pharmacological intervention in hospital). 98 patients were eligible to analysis and 57 (58.16%) were men. 28 of 44 patients(63.64%) in DD+ group and 23 of 54 patients (42.59%) in DD− group had at least one nonfatal CV event or death (p = 0.038). Compared to DD− group, DD+ group had significantly higher incidence of LSCEs (21 vs.14, p = 0.025) and shorter survival time (22.02 ± 12.98 months vs. 26.74 ± 12.59 months, p = 0.046). Kaplan–Meier analysis revealed significantly higher risks of primary endpoint (p = 0.039), and LSCEs (p = 0.040) in DD+ group. Multivariate hazard analysis showed that DD+ group had significantly higher risk of primary endpoint [hazard ratio (HR) 1.59; 95% confident interval (CI) 1.54–1.63], and LSCEs (HR 1.47; 95%CI 1.40–1.55). Ultrasound-assessed diaphragm dysfunction predicts clinical outcomes in HD patients. Trial registration: This study was registered with Chinese Clinical Trials Registry ( www.chictr.org.cn ) as ChiCTR1800016500 on Jun 05, 2018.